Molecular basis of flowering under natural long-day conditions in Arabidopsis. (October 2018) - Song, Young; Kubota, Akane; Kwon, Michael; Covington, Michael; Lee, Nayoung; Taagen, Ella; Laboy Cintrón, Dianne; Hwang, Dae; Akiyama, Reiko; Hodge, Sarah; Huang, He; Nguyen, Nhu; et al.
Abstract Plants sense light and temperature changes to regulate flowering time. Here, we show that expression of theArabidopsis florigen gene, FLOWERING LOCUS T (FT ), peaks in the morning during spring, a different pattern than we observe in the laboratory. Providing our laboratory growth conditions with a red/far-red light ratio similar to open-field conditions and daily temperature oscillation is sufficient to mimic theFT expression and flowering time in natural long days. Under the adjusted growth conditions, key light signalling components, such as phytochrome A and EARLY FLOWERING 3, play important roles in morningFT expression. These conditions stabilize CONSTANS protein, a majorFT activator, in the morning, which is probably a critical mechanism for photoperiodic flowering in nature. Refining the parameters of our standard growth conditions to more precisely mimic plant responses in nature can provide a powerful method for improving our understanding of seasonal response. The usual light conditions used in laboratories fail to mimic natural conditions. Here, by slightly modifying red/far-red ratios and temperature dynamics, the authors are able to faithfully reproduce natural spring flowering times and variation of the FT gene.